Government initiatives and public awareness on HIV/AIDS in Malaysia: where are we after 30 years? - Tham, Jen Sern; Amira Sariyati Firdaus,; Hasmah Zanuddin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
HIV/AIDS has been a growing public health problem in Malaysia for over three decades. To curb the spread of HIV/AIDS and to increase public awareness regarding the disease, numerous initiatives have been developed by various stakeholders. This study is an exploratory investigation of health communication and public awareness of HIV/AIDS, based on a cross-sectional survey of 384 respondents in Klang Valley, Malaysia. The study examines public knowledge of HIV/AIDS and public perceptions of people living with HIV/AIDS (PLHIV) as well as public awareness of public initiatives. The results show that interpersonal channels are important HIV/AIDS informational sources, and that newspapers are a major mass communication or media source for HIV/AIDS information. The public is generally aware of HIV/AIDS transmission, but still harbors moderate, rather than straight-cut positive, perceptions and attitudes towards PLHIV. This shows that the National Strategic Plan on HIV/AIDS may not be fully supported by existing public initiatives.